Students' knowledge and beliefs about reading strategies - Loayza Maturrano, Edward Faustino (2021)
The purpose of the research is to identify students' knowledge and beliefs about reading strategies at the end of basic education. It is also intended to determine the type of correlation between students' fundamental knowledge about reading strategies and their beliefs about reading strategies. The study design is quantitative, descriptive-cross-sectional. The collection of information was carried out through a questionnaire of forty items, which was subjected to a pilot test by test and retest of reliability with 30 students. The respondents were 153 students enrolled in the fifth grade of secondary education in a Public Educational Institution in the district of La Molina. The results show that students have a basic knowledge of reading strategies. Likewise, a medium correlation is evidenced between students' fundamental knowledge about reading strategies and their beliefs about reading strategies. In conclusion, the study suggests some implications for the teaching of reading to students at the Secondary level and shows a medium correlation between the variables: knowledge of reading strategies and beliefs of students' reading strategies.